Effects of Mixing Ratio and Lactic Acid Bacteria Preparation on the Quality of Whole-Plant Quinoa and Whole-Plant Corn or Stevia Powder Mixed Silage - Chao He; Qian Li; Huaidong Xiao; Xuchun Sun; Zepeng Gao; Yuan Cai; Shengguo Zhao (Microorganisms)
Quinoa is the only single plant that can meet all the nutritional needs of human, and its potential for feed utilization has been continuously explored, becoming a prosperous industry for poverty alleviation. In order to further tap the feeding value of whole quinoa, develop quinoa as a feed substitute for conventional crops such as corn, and improve its comprehensive utilization rate, this experiment analyzed the silage quality and mycotoxin content of mixed silage of whole-plant quinoa (WPQ) with whole-plant corn (WPC) or stevia powder(SP) in different proportions, and further improved the silage quality of mixed silage by using two lactic acid bacteria preparations (Sila-Max and Sila-Mix). The quality, microbial population, and mycotoxin levels of quinoa and corn silage, as well as that of the mixed silage of quinoa and stevia, were evaluated using single-factor analysis of variance. The impact of various lactic acid bacteria preparations on the quality of whole-quinoa and whole-corn mixed silage was investigated through two-factor analysis of variance. WPQ and WPC were mixed at the ratio of 5:5 (QB5), 6:4 (QB6), 7:3 (QB7), 8:2 (QB8), 9:1 (QB9) and 10:0 (QB10). SP was mixed with WPQ at the supplemental levels of 0.2% (QB10S2), 0.4% (QB10S4), 0.6% (QB10S6), 0.8% (QB10S8) and 1.0% (QB10S10). After 60 days of silage, the silage indexes, the number of harmful microorganisms, and the mycotoxin levels were measured, to explore the appropriate ratio of mixed silage. The membership function analysis showed that the quality of mixed silage of WPQ with SP was better, and the optimal addition amount of SP was 0.6%. The results of Max and Mix on the quality improvement test of WPQ with WPC mixed silage showed that the two lactic acid bacteria formulations increased CP and AA content, and reduced NH3-N/TN; pH was significantly lower than the control group (p < 0.01), and LA was significantly higher than the control group (p < 0.01). The microbial count results showed that the addition of lactic acid bacteria preparation significantly reduced the number of molds and aerobic bacteria, and the effect of Mix was better than that of Max. When the mixing ratio was between QB7 and QB10, mold was not detected in the lactic-acid-bacteria preparation groups. Max and Mix significantly reduced the levels of mycotoxins, both of which were far below the range of feed safety testing, and 16S rRNA sequencing revealed that the silage microbiota varied with different mixing ratios and whether lactic acid bacteria preparations were used. Max and Mix increased the relative abundance of Firmicutes, with Mix having a more significant effect, especially in the QB6 (65.05%) and QB7 (63.61%) groups. The relative abundance of Lactobacillus was significantly higher than that of the control group (p < 0.05). The relative abundance of Enterobacteriaceae and Streptococcus were negatively and positively correlated with the addition level of quinoa, respectively. Comprehensive analysis showed that adding 0.6% SP to the WPQ and using Mix in mixed silage of WPQ and WPC with the proportion of WPQ no less than 70% had the best silage effect, and was more beneficial to animal health.